Hubungan Konsumsi Fast Food dan Sedentary Lifestyle terhadap Status Gizi Siswa - Athira Demitri; Vivin Martalenta Lase; Yulita Yulita; Tuty Hertati Purba (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
An unbalanced diet can contribute to nutritional problems among adolescents. In addition, changes in adolescents’ lifestyles that tend to lead to a sedentary lifestyle may increase the risk of overweight and obesity. This study aimed to determine the relationship between fast food consumption and sedentary lifestyle with students’ nutritional status. This study employed a descriptive design with a cross-sectional approach. Samples were selected using a purposive sampling technique, involving 118 students. Data were collected through questionnaires and analyzed using the Chi-square test. The results showed that there was no significant relationship between fast food consumption and students’ nutritional status (p = 0.564). However, there was a significant relationship between sedentary lifestyle and students’ nutritional status (p = 0.008). Based on the findings, it can be concluded that a sedentary lifestyle or low physical activity has a greater influence on students’ nutritional status compared to fast food consumption. Therefore, efforts are needed to increase physical activity and reduce sedentary behavior in order to maintain and improve students’ nutritional status.